Efektivitas Pelayanan Prima Bank Muamalat cabang Ponorogo Pada Saat Pandemi Covid-19 - Agus Mujiyono; Muslih Candrakusuma (Universitas Muhammadiyah Ponorogo, 2022)
Corona pandemic caused many losses. Especially on the economic side. Now all public services must be in accordance with the recommended health protocol. Because the country's economic activities must continue to run, therefore the economic activity of the banking sector must also continue. The change in banking services provided follows the existing health protocol. Banking service providers are required to take preventive measures to minimize the spread of the corona virus. Bank Muamalat Cabang Ponorogo branch has also taken various preventive actions and there are e-Channel BMI and BMI call services that can facilitate customers who are at home, and customers can take advantage of BMI ATM outlets in many places to make transactions to minimize coming to the office banks to reduce the risk of spreading the virus.